The formation of hydrogen-deficient stars in binaries - Podsiadlowski, P (2008)
Binary evolution produces a large number of formation channels for hydrogen-deficient stars. Here I review the main binary interactions, stable and unstable mass transfer, binary mergers, and apply them to a variety of objects. including hot subdwarfs, He-rich sdO stars, AM CVn stars, Type Ia supernova progenitors, ultracool white dwarfs and Type Ic and gamma-ray burst progenitors.